A critical overview of the Belgrade Climate Change Adaptation Action Plan - Devetakovic, Mirjana S; Radojević, Milan A (Arhitektura i urbanizam, 2017)
In the European context, the region of the Western Balkans is seen as one significantly affected by the actual climate changes. Using experiences from numerous European cities that are already adapting to their changing climates, the capital cities of the Western Balkans countries are starting to develop strategies of adaptation to actual and expected climate conditions. In this article we give an overview of the document titled Climate Change Adaptation Action Plan with Vulnerability Assessment issued by the City of Belgrade, Secretariat for Environmental Protection. After giving a brief introduction on the document creation within the project Climate Change Adaptation in the Western Balkans and the methodology applied, a structure of the document has been presented highlighting proposed adaptation actions. The paper continues with a critique of the document, main point of which is a lack of indication of financial sources for the proposed actions, as well as interlinking with national adaptation strategies and disaster risk reduction for the parts of the city particularly affected with the floods in 2014. Keywords: climate change, adaptation, actions, Belgrade, Western Balkans